Between Innovation and Legal Vacuum: Evaluating Indonesia’s Criminal Law Readiness Against Deepfake Artificial Intelligence - Annisabella Oktaviani; Dewi Rhosita Hayati; Ema Sarila Sinaga; Defrianus Nong Deris; Irawan, Tony Indra (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2026)
The rapid development of artificial intelligence (AI) enabled the emergence of deepfake technology capable of generating highly realistic manipulated audio and visual content. While offering beneficial applications, its misuse poses serious threats in cybercrime, including digital fraud, defamation, non-consensual pornography, and election-related disinformation. This study aims to evaluate Indonesia’s criminal law system's readiness to respond to deepfake-related misconduct, particularly in light of the principles of legality and legal certainty. Using normative legal research, it analyzes the compatibility between existing Indonesian criminal provisions, such as the Indonesian Criminal Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law, and typical forms of deepfake-related harms, while also comparing developments in the United States of America, the European Union, and China. The findings show that existing regulations only partially address such misconduct and were not designed for AI-generated synthetic media, creating enforcement challenges. This study highlights the urgent need for regulatory reform, including clearer legal definitions, transparency obligations for AI-generated content, and specific provisions to strengthen legal certainty, protect digital rights, and enhance cybersecurity enforcement in practice.